Guardant360 Circulating Tumor DNA Assay Is Concordant with FoundationOne Next‐Generation Sequencing in Detecting Actionable Driver Mutations in Anti‐EGFR Naive Metastatic Colorectal Cancer. (19th November 2019) - Gupta, Rohan; Othman, Tamer; Chen, Chen; Sandhu, Jaideep; Ouyang, Ching; Fakih, Marwan
Abstract: Background: Direct comparisons between Guardant360 (G360) circulating tumor DNA (ctDNA) and FoundationOne (F1) tumor biopsy genomic profiling in metastatic colorectal cancer (mCRC) are limited. We aim to assess the concordance across overlapping genes tested in both F1 and G360 in patients with mCRC. Materials and Methods: We retrospectively analyzed 75 patients with mCRC who underwent G360 and F1 testing. We evaluated the concordance among gene mutations tested by both G360 and F1 among three categories of patients: untreated, treated without, and treated with EGFR inhibitors, while considering the clonal and/or subclonal nature of each genomic alteration. Results: There was a high rate of concordance in APC, TP53, KRAS, NRAS, and BRAF mutations in the treatment‐naive and non–anti‐EGFR‐treated cohorts. There was increased discordance in the anti‐EGFR treated patients in three drivers of anti‐EGFR resistance: KRAS, NRAS, and EGFR somatic mutations. Based on percentage of ctDNA, discordant somatic mutations were mostly subclonal instead of clonal and may have limited clinical significance. Most discordant amplifications noted on G360 showed the magnitude below the top decile, occurred in all three cohorts of patients, and were of unknown clinical significance. Serial ctDNA in anti‐EGFR treated patients showed the emergence of multiple new alterations that affected the EGFR pathway: EGFR and RAS mutations and MET, RAS, and BRAF amplifications. Conclusion: G360 Next‐Generation Sequencing platform may be used as an alternative to F1 to detect targetable somatic alterations in non–anti‐EGFR treated mCRC, but larger prospective studies are needed to further validate our findings. Abstract : This article compares the concordance rate of driver mutations and other significant genomic alterations between the FoundationOne assay (F1) for tissue biopsies and Guardant360 (G360) circulating tumor DNA, focusing on therapeutic implications for patients with metastatic colorectal cancer, based on the two commonly applied tumor next‐generation sequencing platforms.